Sophorolipids as anticancer agents: progress and challenges - Salam Bhopen Singh; Kanupriya Kuniyal; Ananya Rawat; Ananya Bisht; Vijendra Shah; Achlesh Daverey (Discover Oncology)
Abstract Sophorolipids (SLs) are considered effective biosurfactant for cancer treatment, which can efficiently inhibit the viability of various cancer types including breast, lung, liver, cervical and colon cancers. Their mechanism of action targets apoptosis and operates at the level of caspase enzymes, upregulation and downregulation of the B-cell lymphoma (Bcl)-family proteins, and changes in mitochondrial membrane permeability. The binding of SLs to the cancer cell receptors modulates the expression of Bax, APAF1, Bcl-2 and Bcl-x, and triggers the release of cytochrome c into the cytosol which further activates caspase-3/9 pathways leading to apoptosis. SLs also increase intracellular reactive oxygen species (ROS) level in cancer cells that activates pro-apoptotic JNK and p38 MAPK signaling pathways and induce apoptosis through the activation of caspase (3, 6 and 7) pathways. Recently, the integration of anticancer drugs like doxorubicin hydrochloride into SL based nanoparticles (SLNPs) enhanced stability, biocompatibility, bioavailability, pharmacokinetics and therapeutic efficacy. Besides, doxorubicin and resveratrol conjugated NPs induced apoptosis in resistant breast cancer cells by down-regulating the expression of Bcl-2, NF-kB and efflux transporters. However, several challenges exist regarding the stability of SLs under physiological conditions, targeting specific cancer cells, and their clinical applications. This study provides updated concepts on the formulations and properties of different types of SLs, their mechanism of anticancer action and applications in nanotechnology for targeted drug delivery system.